Identification and characterization of prescription drugs that change levels of 7-dehydrocholesterol and desmosterol - Phillip A. Wages; Hye-Young H. Kim; Zeljka Korade; Ned A. Porter (Journal of Lipid Research, 2018)
Regulating blood cholesterol (Chol) levels by pharmacotherapy has successfully improved cardiovascular health. There is growing interest in the role of Chol precursors in the treatment of diseases. One sterol precursor, desmosterol (Des), is a potential pharmacological target for inflammatory and neurodegenerative disorders. However, elevating levels of the precursor 7-dehydrocholesterol (7-DHC) by inhibiting the enzyme 7-dehydrocholesterol reductase is linked to teratogenic outcomes. Thus, altering the sterol profile may either increase risk toward an adverse outcome or confer therapeutic benefit depending on the metabolite affected by the pharmacophore. In order to characterize any unknown activity of drugs on Chol biosynthesis, a chemical library of Food and Drug Administration-approved drugs was screened for the potential to modulate 7-DHC or Des levels in a neural cell line. Over 20% of the collection was shown to impact Chol biosynthesis, including 75 compounds that alter 7-DHC levels and 49 that modulate Des levels. Evidence is provided that three tyrosine kinase inhibitors, imatinib, ponatinib, and masitinib, elevate Des levels as well as other substrates of 24-dehydrocholesterol reductase, the enzyme responsible for converting Des to Chol. Additionally, the mechanism of action for ponatinib and masitinib was explored, demonstrating that protein levels are decreased as a result of treatment with these drugs.